IMPACT OF FISH WASTE PROTEIN ENZYMETIC HYDROLYSATE ON GROWTH OF SOME OF Lactobacillus sp. AND Bifidobacterium sp. - A. S. Mohammed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate the impact of protein enzymatic hydrolysate extracted from waste of common carp (Cyprinus carpio) on some bacterial growth. Two type protein concentrates were prepared from defatted carp fish waste powder, the first at pH 2/4.5 and the second at pH 12/4.5. They were hydrolysed by pepsin enzyme lyophilized powder ≥ 2500 units/mg conc.1.5gm/100gm protein concentrates for (30, 60, 90, and 120) minutes. The obtained hydrolysates characterized in term of color, amino acids, minerals elements, degree of hydrolysis, solubility in addition to bacterial growth promotor and biomass production properties. The whiteness of acidic and basic protein concentrates were (68.62 and 67.09) %, respectively, their content of essential amino acids were (35.73 and 34.5)%, respectively, they contained similar concentrations of mineral elements. The highest degree of hydrolysis for the concentrate was acheived after 120 minutes of enzymatic reaction time, being (50.8 and 52.4)%, their solubilities were increased with increasing enzymatic reaction time, and highest values were recorded at pH 2 and 10. Number of colonies and biomass of  Bifidobacterium infantis, Lactobacillus plantarum and Lactobacillus rhamnosus GG was in alternative media higher than commercial medium (MRS) .